Executive Function Moderates Functional Outcomes of Engagement Strategies During Rehabilitation in Older Adults. (July 2021) - Ercal, Baris; Rodebaugh, Thomas L.; Bland, Marghuretta D.; Barco, Peggy; Lenard, Emily; Lang, Catherine E.; Miller, J. Philip; Yingling, Michael; Lenze, Eric J.
Abstract : Objective: This study examined cognitive, affective, and medical impairments and their impact on rehabilitation approaches for improving functional outcome after hospitalization in older adults. Design: A secondary analysis of a randomized clinical trial in 229 adults 65 yrs or older admitted to two skilled nursing facilities undergoing rehabilitation services was conducted. Patients were randomized to receive physical and occupational therapy by therapists trained in systematic approaches to engage patients, called Enhanced Medical Rehabilitation, or standard of care. The outcome of interest was functional improvement, defined as Barthel Index at discharge (controlling for Barthel Index upon admission). This study analyzed the relationship of measures of cognition, depression, and medical comorbidities as predictors of functional outcome and as moderators interacting with treatment group. Results: Clock drawing score moderated treatment effect size; the functional improvement of Enhanced Medical Rehabilitation over standard of care therapy reduced with increasing executive impairment. In contrast, general cognitive abilities, depression, medical comorbidities, and readiness for rehabilitation were neither predictors nor moderators of functional improvement. Conclusions: For older adults undergoing rehabilitation, greater functional improvement with the motivational techniques of Enhanced Medical Rehabilitation was contingent on patients having intact executive function. Given that executive function impairments are common in rehabilitation populations, new strategies are needed to improve treatment outcomes in physical/occupational therapy. To Claim CME Credits: Complete the self-assessment activity and evaluation online at http://www.physiatry.org/JournalCME CME Objectives: Upon completion of this article, the reader should be able to (1) Discuss the role of baseline affective, cognitive, and medical impairments in impacting functional outcomes of older adults undergoing rehabilitation; (2) Describe the behavioral change and motivational approaches that are core features of the novel intervention known as Enhanced Medical Rehabilitation (E-MR); and (3) Determine the role of baseline executive function in moderating the effect of rehabilitation intervention on functional outcomes in older adults. Level: Advanced Accreditation: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians. The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 1.0 AMA PRA Category 1 Credit(s)™ . Physicians should only claim credit commensurate with the extent of their participation in the activity.